Transformasi Pengembangan Materi Pendidikan Agama Islam dengan Nilai Islam Indonesia (dari Pendekatan Monodisipliner menuju Pendekatan Interdisipliner) - Hawwin Muzakki; Ahmad Natsir; Ahmad Fahrudin (Journal of Islamic Education Research, 2021)
Islamic Education is open to any ideas that come from other knowledge clumps. This open-access should make Religion teachers think about conveying the perspective of Islam using an interdisciplinary rather than monodisciplinary approach. This study initiated the development of Islamic Education material using an interdisciplinary approach, with the following problem formulations: first, what are the concepts and weaknesses of Islamic Education material development using a monodisciplinary approach? second, how does the concept offer Islamic Education material development using an interdisciplinary approach? The purpose of this study is to transform the development of Islamic Religious Education material with Indonesian Islamic values. By using a qualitative approach, content analysis, and qualitative descriptive methods. This study concludes: first, the concept of developing Islamic Education material using a monodisciplinary approach still uses only one clump of religious knowledge in its delivery, which results in an exclusive understanding of religion. Second, the concept of Islamic Education learning that uses an interdisciplinary approach can present religious studies by involving social studies, humanism, environmental issues, gender, Indonesianness, and politics.